Adsorptive removal of malachite green and Rhodamine B dyes on Fe3O4/activated carbon composite - KERKEZ KUYUMCU, ÖZGE (TAYLOR & FRANCIS INC, 2017)
This study demonstrates the adsorption experiments of toxic dyes malachite green (MG) and Rhodamine B (RB) on Fe3O4-loaded activated carbon (AC). AC, which is known to be a high-capacity adsorbent, was aimed to be easily separated from aqueous media by loading it with Fe3O4. Fe3O4-loaded AC was prepared by the coprecipitation method and named magnetic activated carbon (M-AC), and the produced M-AC was characterized by x-ray diffraction (XRD), thermogravimetric analysis (TGA), and pH(pzc) analyses. MG and RB adsorption by the M-AC was performed separately by batch technique and the effects of adsorbent amount, solution pH, and initial dye concentration on the adsorption were explored. Maximum removal efficiencies were found to be 96.11% for MG and 98.54% for RB, and the Langmuir isotherm model was the most fitted isotherm model for the adsorption. The kinetic and thermodynamic studies showed that the adsorption proceeded via the pseudo-second-order kinetic model and endothermic in-nature for both dyes.
Keywords: Activated carbon; adsorption; magnetic separation; malachite green; Rhodamine B; ACTIVATED CARBON; AQUEOUS-SOLUTION; METHYLENE-BLUE; ISOTHERM; EQUILIBRIUM; KINETICS; NANOPARTICLES; OPTIMIZATION; NANOTUBES; ADSORBENT